Effects of oligosaccharide-sialic acid (OS) compound on maternal-newborn gut microbiome, glucose metabolism and systematic immunity in pregnancy: protocol for a randomised controlled study - Yu Liu; Shuxian Wang; Rui Peng; Shengtang Qin; Huixia Yang; Jingmei Ma (BMJ Open)
Introduction The gut microbiota participates in multiple human biological processes, including metabolism and immune responses. During pregnancy, the dynamics of gut microbiota is involved in physiological adaptation. The disturbed profile of microbiome is associated with maternal complications, such as gestational diabetes mellitus (GDM), which further transfers to the offspring and influence their metabolic and immunological functions in the long term. Prebiotics targeting the gut microbiota and modulating metabolic and immune functions have been shown to be effective in non-pregnant populations with metabolic syndrome. Hence, we propose the use of a prebiotic supplement, oligosaccharide-sialic acid (OS) from the first trimester until delivery in pregnant women, can benefit maternal/new-born gut microbiome, glucose metabolism and innate immunity.Methods and analysis In this prospective double-blinded randomised clinical trial, recruited singleton pregnancies will be stratified by body mass index (BMI) and randomly assigned to consume the OS preparation or placebo daily from the first trimester. At seven later time points (before and after recruitment in the first trimester, in the middle and third trimesters, before delivery, at birth and 42 days postpartum), compliance will be evaluated and/or biological samples will be collected. Along with maternal clinical information, questionnaires on lifestyle and infant development will be recorded. The primary outcomes are the effect of OS on the maternal-offspring gut microbiome and GDM incidence. The secondary outcomes are maternal glycolipid biochemical parameters, cytokine profiles, weight gain during pregnancy and infant morbidities, growth and development. The study aims to validate the effects of OS on reducing maternal morbidity within different BMI groups. The multiple dimensional dataset generated from the study includes clinical and lifestyle-related information, various biological markers and associated protective or risk factors for morbidity and prognosis. An extended follow-up through 42 days after birth could further explore the intrauterine influence on the long-term health of offspring.Ethics and dissemination This protocol has been approved by Peking University First Hospital, National Unit of Clinical Trial Ethics Committee (reference number: 164). The results are expected to be published in scientific manuscripts by 2021.Trial registration number ChiCTR1800017192.